Existence of solutions for non-necessarily cooperative systems involving Schrödinger operators - Laure Cardoulis (International Journal of Mathematics and Mathematical Sciences)
We study the existence of a solution for a non-necessarily cooperative system of n equations involving Schrödinger operators defined on ℝN and we study also a limit case (the Fredholm Alternative (FA)). We derive results for semilinear systems.